Otitis externa and myringitis due to demodicidosis - Klemm, Eckart (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
We report on an 84-year-old woman with chronic pruritic otitis externa and myringitis. Microbiological and mycological investigations failed to establishthe cause, but histology revealed a large amount of Demodex mites. Topical treatment for this ectoparasite resulted in a complete remission. The myringitis was eventually treated successfully with myringoplasty. To the bestof our knowledge this is the first case report on Demodex-induced otitis externa and myringitis.
Keywords: dermatologija; kožne spremembe; otitis